Extraction of lantana camara for wound healing application - Nurul Fahana, Abdul Pattah (2013)
Lantana camara L. is one of the plants that are central to the lives of traditional societies in India. It has been reported as a traditional folkloric medicine for the variety of diseases. The plant leaves are also used in some parts of India for wound healing, but there are no scientific reports on any wound healing activity of the plant. The aim of this experiment is to investigate the extraction of Lantana camara L. for wound healing application. Phytochemical Screening is used to determine the composition in the extract oil. The wound healing activity of Lantana camara L. Was studied by incorporating the hydro extraction in pure vaselline in a concentration of 5 % and 10% (w/w) and observe the percentage of wound closure in the control and extract treated groups. As a result, the percentage of wound closure will increase due to time on the treated group with 10 % extract compared with 5 % extract while control group takes more time for wound healing activity. This proves the significance studied that Lantana Camara L. can be applied as a wound healing agent.